2009
DOI: 10.1038/nature07916
|View full text |Cite
|
Sign up to set email alerts
|

Tbx18 and the fate of epicardial progenitors

Abstract: Uncovering the origins of myocardial cells is important for understanding and treating heart diseases. Cai et al. suggest that Tbx18-expressing epicardium provides a substantial contribution to myocytes in the ventricular septum and the atrial and ventricular walls. Here we show that the T-box transcription factor gene 18 (Tbx18) itself is expressed in the myocardium, showing that their genetic lineage tracing system does not allow conclusions of an epicardial origin of cardiomyocytes in vivo to be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
204
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(215 citation statements)
references
References 15 publications
10
204
0
1
Order By: Relevance
“…1 G-I), indicating that the epicardium is likely to be the sole source of EAT adipocytes. However, it should be cautioned that additional nonepicardial sites of Tbx18Cre expression (22,23) could in principle contribute cells to this tissue.…”
Section: Discussionmentioning
confidence: 99%
“…1 G-I), indicating that the epicardium is likely to be the sole source of EAT adipocytes. However, it should be cautioned that additional nonepicardial sites of Tbx18Cre expression (22,23) could in principle contribute cells to this tissue.…”
Section: Discussionmentioning
confidence: 99%
“…112 These findings have been challenged by others. 116 Furthermore, it is current textbook knowledge that the epicardium forms the coronary vessels. A very recent study indicated in contrast that the coronary arteries form by developmental reprogramming of venous cells.…”
Section: A Third Cardiac Lineage: the Epicardiummentioning
confidence: 99%
“…Although the chicken model demonstrates highly reproducible results, the results described in the current work could possibly be strengthened by electrophysiological testing in a mammalian model, which shows defects in epicardial covering. However, up to date, there is no mouse model specifically affecting outgrowth of the epicardium, since the genes commonly used for epicardium-specific expression of Cre are known to be expressed more broadly throughout the fetus during development [19,45].…”
Section: Discussionmentioning
confidence: 99%